Development of plants morphology characteristics textbook to improve students’ ability in identifying plants - Angreni Beaktris Liunokas; Agsen Hosanty Susana Billik (JPBIO (Jurnal Pendidikan Biologi), 2022)
The selection and use of appropriate textbooks in the lecture process is an important factor for improving science process skills. This study aims to develop textbooks on plant morphological characteristics that are valid, practical, and effective in increasing students' ability to identify plants. The method used is research and development with a design Plomp model which consists of five stages in the form of (1) initial investigation, (2) design, (3) realization, (4) testing, evaluation, and revision, (implementation). The subjects of this study were students who took plant anatomy and morphology courses, the academic year 2020/2021 of the STKIP Soe Biology education study program. Data collection techniques in the form of observation, tests, and questionnaires. The product in the form of a textbook developed was tested for validity based on the research results of the expert team as a validator. The practicality of the product was tested using a student and lecturer response questionnaire analysis. The textbook effectiveness test was carried out through quasi-experimental research with analytical techniques using an independent sample T-test and normalized gain scores. The results showed that the textbooks developed were valid, practical, and effective to improve students' ability to identify plant species.